Book reviews - JNAAT (Journal of Numerical Analysis and Approximation Theory)
Andrei Stan: David L. Chopp, Introduction to High Performance Scientific Computing, SIAM, Philadelphia, 2019, ISSN: 9781611975642, ISSN (print): 9781611975635.